Atypical (bizarre) leiomyoma of the nasal cavity with prominent myxoid change. Issue 11 (1st November 2002) - Vincenzi, A; Rossi, G; Monzani, D; Longo, L; Rivasi, F
Abstract : A 72 year old woman presented complaining of nasal obstruction, rhinorrea, and epistaxis. At examination, a polypoid mass on the right posterior choana was revealed and subsequently removed. Light microscopic findings consisted of a diffuse proliferation of spindle shaped, pleomorphic cells with eosinophilic cytoplasm and blunt ended nuclei in a prominent myxoid background. The presence of numerous plurinucleate, bizarre cells made it very difficult to determine the malignant potential. Immunohistochemical evidence for leiomyogenic markers coupled with the low mitotic rate, the lack of an infiltrating growth pattern, and the indolent clinical course led to the diagnosis of atypical leiomyoma with prominent myxoid change. A literature survey confirmed that such a tumour is extremely rare at this site, but the biological behaviour seems to be similar to its uterine counterpart. Clinicians should be aware of this occurrence to prevent misdiagnosis because a conservative therapeutic approach is necessary in this disease.